2002
DOI: 10.1017/s0950268802007379
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an outbreak of cercarial dermatitis

Abstract: We present the investigation of an outbreak of cercarial dermatitis that occurred in a recreational-tourist lake in the Quebec City region (Canada) in the summer of 1999. A case-reporting form was sent to 450 families likely to have activities that would bring them in contact with the lake's water. The snails were characterized and the prevalence of their infestation by schistosomes was investigated. In total, 63 episodes consistent with cercarial dermatitis were reported. Sixty-nine percent of the cases occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309). There are rare cases of nonsensitive individuals that may be due to host desensitization (310) or individual nonsusceptibility/nonattractivity to cercariae (4,311).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
See 3 more Smart Citations
“…For example, longer exposure in water increases cercarial penetration via frequent water visits and more time spent in shallow water (4,(304)(305)(306). While gender does not influence the risk of infection (4,304,305,307), some studies found a higher risk among children of less than 15 years of age, since they tend to spend more time in shallow water (280,308,309). There are rare cases of nonsensitive individuals that may be due to host desensitization (310) or individual nonsusceptibility/nonattractivity to cercariae (4,311).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
“…Locally, the highest risk of infection usually occurs in shallow, warm, and vegetation-rich shore areas, where the snails accumulate and release cercariae (308,309). Cercariae of avian schistosomes are concentrated just beneath the water surface (see the information on host finding), so swimming in deeper water may reduce the infection probability (280).…”
Section: Recreational Activities and Cercarial Dermatitismentioning
confidence: 99%
See 2 more Smart Citations
“…The age groups were classified in 7 levels and each level was 10 years younger than the next. There were 338 people in age groups of [10][11][12][13][14][15][16][17][18][19] years old, 565 people (24.5%) in the group of 20-29 years old, 459 people in the age group of 30-39 years old, 427 people in age group of 40-49 years old, 507 people in the age group of 50-59 years old, 9 people in the age group of 60-69 years old and 5 people in age group of more than 70 years old. From the vocational point of view, the people under study were divided into 5 job groups which are: householders, clerks, farmers, university or school students, other vocations and self-employments.…”
Section: Methodsmentioning
confidence: 99%